Aktiv effektstyrning för flaskhalshantering i regionnät - Amundsson,Erika; Andersson,Sofia (CODEN:LUTEDX/TEIE, 2025)
The aim of this master's thesis is to investigate the potential of active power flow control to mitigate bottlenecks through the implementation of phase-shifting transformers (PST) and static synchronous series compensators (SSSC). The report is based on a case study of E.ON's sub-transmission network in the southern part of Sweden, where these components are introduced to mitigate future bottlenecks predicted to occur by 2034 if no reinforcement of the grid is implemented. The program Power System Simulator for Engineering (PSSE) is utilized to model these devices and perform static load flow analysis to assess the potential of these components. The findings show that both PST and SSSC are able to effectively reduce overloads on transmission lines, achieving a reduction of line loading to ≤ 90% of its capacity in all investigated scenarios. Furthermore, results reveal that this can be achieved through the installation of three PST units at two separate locations with phase-shift capability within ±20 degrees, or alternatively, with the installation of 11 SSSC modules distributed across five locations. These results are obtained through the chosen placement strategy that involves replacing system transformers with PSTs and installing SSSC units directly on overloaded lines. Both PST and SSSC offer a cost-effective alternative to traditional grid reinforcement strategies. Among these options, replacing a system transformer that is due for exchange with a PST is the most cost-effective approach, although the SSSC remains the most affordable solution for direct intervention. Furthermore, the installation of SSSC can be completed within 1 to 2 years, significantly faster than PST-installation or line reinforcement, which typically require over 5 years. Overall, the findings in this report suggest that strategic implementation of PST and SSSC can play a crucial role in managing future grid constraints and optimizing power distribution within E.ON's sub-transmission network.
Keywords: Aktiv effektflödeskontroll; Flaskhalsar; Regionnät; Maskat nät; Fasvridande transformatorer; PST; Flexibla AC Transmissionsystem; FACTS; Statisk synkron seriekompensator; SSSC